Metode studio oriented learning environment untuk meningkatkan kualitas belajar mahasiswa dalam studio perancangan interior - Ully Hanafiah; Doddy Friestya Asharsinyo (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2021)
Due to the complexity of activities and interior elements in the studio-oriented learning environment, it is essential to apply the right method in all stages to ensure they proceed sequentially and systematically. This is because presently the in-depth design method associated with this learning environment has not been fully explored to fulfill user needs in accordance with the design project. Therefore, this research aims to determine the right method used to improve students learning quality in the teaching process at the Interior Design studio, to obtain better responses. This research was carried out using the CAR model proposed by Kemmis and Mc Taggart consisting of four components, namely planning, action, observation, and reflection. The result showed that after the re-planning process, a reflection in the form of a separate cycle is conducted. Furthermore, independent learning methods in a conducive environment are carried out based on the Studio Oriented Learning Environment (SOLE) method, with assessments conducted by lecturers and students in each assistance group. This research has the ability to improve students thinking ability sequentially and systematically, as well as increase their participation and collaboration in producing quality designs.